The Mid-Diaphysis Is a Poor Predictor of Humeral Fracture Risk Indicating That Predisposing Factors Are Recent - Gibson M; Dittmer K; Hickson R; Back P; Wehrle-Martinez A; Rogers C (MDPI (Basel, Switzerland), 2021)
The incidence of spontaneous humeral fractures in first-lactation dairy heifers in New Zealand has emphasised the need to understand the thoracic limb bone growth of dairy heifers. Previous research has indicated that a predisposing factor to spontaneous humeral fracture is nutrition. In addition, it has been hypothesised that liver copper concentration affects bone strength and may be a potential factor associated with humeral fracture risk. The aim of this study was to compare bone morphology in the mid-diaphysis of the metacarpus and humerus of heifers affected and unaffected by spontaneous humeral fractures, and determine the effect of copper status at death on bone morphology. The metacarpus and humerus were collected from heifers affected and unaffected by humeral fractures, and scanned using peripheral quantitative computed tomography (pQCT). The mid-diaphysis of the humerus of the affected group had reduced cortical bone mineral density and a trend for reduced cortical content and total bone content, which contributed to a reduced stress–strain index. The trend for reduced bone length in affected humeri provides additional support for the hypothesis of inhibited humeral growth. Heifers with low copper liver concentrations had reduced humerus lengths and reduced cortical bone mineral densities. These data support the hypothesis that the developmental window for humeral fracture is recent, and possibly associated with periods of inadequate nutrition.
Keywords: bone strength; fracture; humerus; metacarpal; pQCT; mid-diaphysis